Establishing the Essential Zone: Free Gingival Graft for Gingival Augmentation and Root Coverage - Sapkota, Pratik; Shrestha, Sajeev; Adhikari, Khushbu; Acharya, Pujan; Thapa, Victory (Journal of Nepalese Society of Periodontology and Oral Implantology, 2023)
Gingival recession is a frequently encountered clinical finding which causes compromised aesthetics and dentinal hypersensitivity leading to an inadequate zone of keratinized gingiva and might facilitate subgingival plaque formation resulting in further attachment loss. Epithelized soft tissue graft harvested from the hard palate, commonly known as free gingival graft is simple and highly predictable when used to increase the amount of keratinized tissue. This case report highlights the use of free gingival graft as a gingival augmentation and root coverage procedure for 26-year-old patients with Cairo RT2 mucogingival defects with optimum aesthetic outcome.